Sometimes they come back: New and old spinal muscular atrophy adults in the era of nusinersen. (31st October 2020) - Sansone, V. A.; Coratti, G.; Pera, M. C.; Pane, M.; Messina, S.; Salmin, F.; Albamonte, E.; De Sanctis, R.; Sframeli, M.; Di Bella, V.; Morando, S.; d'Amico, A.; et al.
Abstract : Background and purpose: Following the commercial availability of nusinersen, there have been a number of new referrals of adults with spinal muscular atrophy (SMA) not regularly followed in tertiary‐care centers or enrolled in any disease registry. Methods: We compared demographics and disease characteristics, including assessment of motor and respiratory function, in regularly followed patients and newcomers subdivided according to the SMA type. Results: The cohort included 166 adult patients (mean age: 37.09 years): one type I, 65 type II, 99 type III, and one type IV. Of these 166, there were 67 newcomers. There was no significant difference between newcomers and regularly followed patients in relation to age and disease duration. The Hammersmith Functional Motor Scale Expanded and Revised Upper Limb Module scores were higher in the regularly followed patients compared to newcomers in the whole cohort and in both SMA II and II. A difference was also found on ventilatory status ( p  = 0.013) and Cobb's angle >50° ( p  = 0.039) between the two subgroups. No difference was found in scoliosis surgery prevalence ( p > 0.05). Conclusions: Our results showed differences between the two subgroups, even if less marked in the type III patients. In the type II patients, there was a higher proportion of newcomers who were in the severe end of the spectrum. Of the newcomers, only approximately a third initiated treatment, as opposed to the 51% in the regularly followed patients. The identification of patients who were not part of the registries will help to redefine the overall prevalence of SMA and the occurrence of different phenotypes. Abstract : Percentages of regularly followed patients and newcomers.